El crédito eclesiástico y la economía agraria en Antioquia, 1670-1800 (2013)
ABSTRACT: This article analyzes the development of the crédito eclesiástico (church credit) in the agrarian economy of Antioquia between the seventeenth and eighteenth centuries. First, it introduces the concept of church credit and the agricultural context where it operated. Second, it will deepen the impact of the credit on issues such as land markets, agricultural investment and social shaping.